Optimization of Data Transfer in Cooperative Surveillance Systems - Обод, І. І.; Свид, І. В.; Мальцев, О. С.; Воргуль, О. В.; Майстренко, Г. В.; Заволодько, Г. Е. (PIC S&T, 2018)
In the paper, based on the consideration of the problem of detecting signals in cooperative observation systems as a test of two hypotheses, the optimal rule for detecting signals in the case of an arbitrary cost function is obtained and it is shown that the best value for the Bayesian value should be compared with the threshold of the generalized likelihood ratio, and the threshold value does not depend on the algorithm and the quality of the interrogator, but is completely determined by the decision costs for the system as a whole. The method of the response signals processing of cooperative observation systems with preliminary inter-period processing proposed in the work allowed to improving the quality of air objects detection and reducing the effect of the aircraft’s responder readiness factor on the quality of the air facility detection, which leads to a corresponding improvement in the quality of information support for decision-makers.
Оптимізація передачі даних в кооперативних системах спостереження
Keywords: cooperative surveillance systems; aircraft responder; quality of information support; information support; response signal; readiness coefficient